ANALYSIS OF EFL STUDENTS’ CITATION PRACTICES AND PROBLEMS IN ACADEMIC WRITING - Yanti Sri Rezeki (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2018)
Abstract: Citing sources correctly is vital in academic writing including research proposals. Despite its significance, students seem to perform it poorly due to lack of knowledge and awareness of its role in their writing. As the result, they are often accused of committing plagiarism. One of the ways to prevent students from committing plagiarism is by providing them with sufficient knowledge and skills related to proper citations. This study is a preliminary effort to identify student citation practices within the English Education department of a state university in West Kalimantan, Indonesia. Employing qualitative content analysis, the researcher examined samples of students’ proposals to describe the ways in which citations were written and the common problems that occurred. The findings suggest that students mostly cited as non-integral/non-reporting. The study also reveals that students’ most common mistakes in the citation are found in language and content. The study concludes with the need to provide students with clear guidelines for citation and strong remarks on plagiarism.